Diagnostic value of blood inflammatory markers for detection of acute appendicitis in children - Sack, Ulrich (BioMed Central, 2006)
BACKGROUND: Acute appendicitis (AA) is a common surgical problem that is associated with an acute-phase reaction. Previous studies have shown that cytokines and acute-phase proteins are activated and may serve as indicators for the severity of appendicitis. The aim of this study was to compare diagnostic value of different serum inflammatory markers in detection of phlegmonous or perforated appendicitis in children. METHODS: Data were collected prospectively on 211 consecutive children. Laparotomy was performed for suspected AA for 189 patients. Patients were subdivided into groups: nonsurgical abdominal pain, early appendicitis, phlegmonous or gangrenous appendicitis, perforated appendicitis. White blood cell count (WBC), serum C-reactive protein (CRP), interleukin-6 (IL-6), tumor necrosis factor α (TNF-α), acid α(1)-glycoprotein (α(1)GP), endotoxin, and erythrocyte sedimentation reaction (ESR) were estimated ad the time of admission. The diagnostic performance was analyzed using receiver operating characteristic (ROC) curves. RESULTS: WBC count, CRP and IL-6 correlated significantly with the severity of appendiceal inflammation. Identification of children with severe appendicitis was supported by IL-6 or CRP but not WBC. Between IL-6 and CRP, there were no significant differences in diagnostic use. CONCLUSION: Laboratory results should be considered to be integrated within the clinical assessment. If used critically, CRP and IL-6 equally provide surgeons with complementary information in discerning the necessity for urgent operation.